2014
DOI: 10.1039/c4ra08674k
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sintering additives on densification and Li+ conductivity of Al doped Li7La3Zr2O12 lithium garnet

Abstract: Al–LLZ with 1 wt% of Li4SiO4 added and sintered at 1200 °C was found to be relatively dense which enhances the total (bulk + grain-boundary) Li+ conductivity by reducing the grain-boundary contribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
88
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 31 publications
1
88
0
Order By: Relevance
“…More recently, additives of sintering as LiBO 2 , Li 3 BO 3 , Li 3 PO 4 , and Li 4 SiO 4 have shown positive effects for reducing the sintering temperature and maintaining high conductivity [14,[17][18][19]. Tadanaga and a coworker reported Li-ion conductivity of 1 × 10 −4 S cm −1 at 30°C using Li 3 BO 3 as an additive to pristine LLZO-Al, prepared at the lower sintering temperature of 900°C [14].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…More recently, additives of sintering as LiBO 2 , Li 3 BO 3 , Li 3 PO 4 , and Li 4 SiO 4 have shown positive effects for reducing the sintering temperature and maintaining high conductivity [14,[17][18][19]. Tadanaga and a coworker reported Li-ion conductivity of 1 × 10 −4 S cm −1 at 30°C using Li 3 BO 3 as an additive to pristine LLZO-Al, prepared at the lower sintering temperature of 900°C [14].…”
Section: Introductionmentioning
confidence: 95%
“…The adequate concentration of the additive is a key parameter. The Li-ion conductivity in the garnet electrolyte showed variation of more than one order of magnitude as a function of the additive concentration [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…18,32 The peak at ∼750 cm −1 could be due to the stretching modes of TaO 6 octahedra. 33 Electrical conductivity.-Typical AC impedance spectra of Li 6 La 3 Ta 1.5 Y 0.5 O 12 prepared using 2.5 to 15 wt.…”
Section: CMmentioning
confidence: 99%
“…11 Attempts have also been made to reduce the sintering temperature and improve the control of stoichiometry via wet chemical synthesis as well as through additives acting as sintering aids. [12][13][14][15][16][17][18] It has been shown that Al migrates from the alumina crucible used for garnet synthesis, causing significant effects in the material including stabilization of the cubic phase. [15][16][17][18] Lithium salts such as Li 2 20 They also found that the glassy-like phase formed at the grain-boundaries increases the density of material as well as helps to decrease the grain-boundary and improve the total Li + conductivity.…”
mentioning
confidence: 99%
“…Li-ion conductivity of Li6.625La3Zr1.625Ta0.375O12 sintered at 1000 °C (24 h) with 29 mol% Al [12] reaches 5 × 10 -4 S/cm. Other compounds used as sintering additives include Li2O, Li3BO3, Li3PO4 and Li4SiO4 [13][14][15][16][17][18]. These materials act as binder between the garnet particles during the sintering treatment by the formation of liquid phases at low temperatures, reducing the grain boundary resistance and improving the Li-ion conductivity pathway.…”
mentioning
confidence: 99%